Detailed simulation of distance protection for its testing and setting; Journal of Electrical Engineering; Vol. 69, № 3 - Ruban N. Yu. Nikolay Yurievich; Andreev M. V. Mikhail Vladimirovich; Ufa R. A. Ruslan Alexandrovich; Suvorov A. A. Aleksey Aleksandrovich; Gusev A. S. Alexander Sergeevich (2018, 2018)
Title screen